New regioselective synthesis of polyfunctionalized 3-ferrocenyl-1H-pyrroles under microwave irradiation. Issue 41 (12th October 2016) - Bonacorso, Helio G.; Libero, Francieli M.; Dal Forno, Gean M.; Pittaluga, Everton P.; Back, Davi F.; Hörner, Manfredo; Martins, Marcos A.P.; Zanatta, Nilo
Graphical abstract: Highlights: 2-Azido-3-ferrocenyl acrylate as an excellent precursor for pyrrole's synthesis. Polyfunctionalized 3-ferrocenyl-1 H -pyrroles synthesized under microwave irradiation. High regioselectivity of the cyclization reaction due the ferrocenyl substituent. Abstract: A facile and regioselective synthesis of a series of new methyl 3-ferrocenyl-1 H -pyrrole-2-carboxylates obtained from methyl ferrocenyl azido acrylate and symmetrical or non-symmetrical 1, 3-dicarbonyl compounds under microwave-assisted conditions is reported. 3-Ferrocenyl substituted pyrroles, which are normally difficult to obtain via the known reported methods, can now be regioselectively prepared by this protocol. Compared to already known acidic, basic, or metal-catalyzed methodologies for polysubstituted pyrrole synthesis, the present synthetic route is mild, quick, simple, and it furnishes new functionalized tetrasubstituted-pyrroles in short reaction times (30 min) and at satisfactory to good yields (32–75%).